Modélisation spatio-dynamique de la structure urbaine et du système de transport. - Brice, Stéphane. (University of Ottawa (Canada), 1990)
It appears difficult to explain the spatial organization of a major urban centre without referring to its transportation system just as travel demand analysis and transport planning cannot be dissociated from the understanding of urban structure. Moreover, in economics, transportation is seen as a demand resulting from economic activities while in geography, human interactions are considered as an organizing factor rather than a product of such activities. Consequently we are interested by a modelling framework which can conciliate both realities often analysed separately. Several fundamental hindrances are therefore encountered. Transportation system analysis must initially be integrated within its own components of demand and supply. As for the urban structure, we must seek a representation suited to apprehend the spatial distribution and the evolution of several interdependent activities. Unification also requires definitions of common or at least consistent principles, standardized formulations and an adjustment of temporal scales. This attempt of integration does not imply starting over but rather using all theoretical frameworks, approaches and models concerned by urban structure and transportation. This comprehensive exercise leads to a formulation of a space-time model of a urban region. An empirical application to the Montreal metropolitain area unveils the analytical possibilities, the necessary adjustment and the limitations of this modelling.
Keywords: Geography.